1981
DOI: 10.1002/1097-0142(19810115)47:2<402::aid-cncr2820470231>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The practicality of chronic hepatic artery infusion therapy of primary and metastatic hepatic malignancies: Ten-year results of 124 patients in a prospective protocol

Abstract: Ten-year results are presented of 124 patients with malignancy apparently limited to the distribution of the hepatic artery, treated to prospective protocol with continuous infusion of 5-FUdR through an hepatic artery catheter. Nearly all patients had moderate to massive hepatic replacement. Of 88 patients with colorectal carcinoma, 64 (73%) had clinically objective and subjective remission. Median survival for responders was 13 months; for the entire group, ten months. Of 13 patients with hepatoma, nine had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…All of these variables may influence the response rate and make it difficult to put this treatment modality into perspective. The overall response rate of 50% in this study is comparable to those obtained in previous studies employing 5-FU or FUDR given by continuous hepatic artery infusion [15][16][17][18][19][20][21][22][23]25271. Survival appears similar, with a twofold increase in responders versus nonresponders.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…All of these variables may influence the response rate and make it difficult to put this treatment modality into perspective. The overall response rate of 50% in this study is comparable to those obtained in previous studies employing 5-FU or FUDR given by continuous hepatic artery infusion [15][16][17][18][19][20][21][22][23]25271. Survival appears similar, with a twofold increase in responders versus nonresponders.…”
Section: Discussionsupporting
confidence: 84%
“…In a neoplasm where liver involvement is frequent and affects survival, the use of hepatic artery infusion (HAI) has a sound rationale [ 10-141. In the last two decades a number of investigators have reported results of treatment of metastatic colorectal carcinoma employing either prolonged continuous ( 2 21 days) [15][16][17][18][19][20] or short-term ( < 2 1 days) [21-241 infusion with 5-FU or FUDR alone or in combination [25,26] with other chemotherapeutic agents. Response rates have been variable but range from 34% to 73 %, with an average about 50%.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The delivery of drugs directly into an area of the body affected by carcinoma offers several theoretical advantages for improving the efficacy of existing antineoplastic agents. Extensive clinical experience with regional infusion chemotherapy has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s, there have been numerous reports of infusional therapy for hepatic neoplasms. '3233, 5 The widest experience has been with colorectal carcinoma. An isolated case of metastatic ovarian carcinoma was reported by Scarebelli and Campagnatta. '…”
Section: Discussionmentioning
confidence: 99%